2012
DOI: 10.1016/j.jiph.2011.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Scrub typhus in children at a tertiary hospital in southern India: Clinical profile and complications

Abstract: High incidences of myocarditis and acute kidney injury were observed, which indicates that the children were treated at a late stage of the disease. Clinicians should be cognizant that myocarditis and acute kidney injury are serious manifestations of pediatric scrub typhus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

44
134
17

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(208 citation statements)
references
References 18 publications
44
134
17
Order By: Relevance
“…Studies from other parts of India and other countries have reported a similar age distribution. 9,10,[18][19][20] Male preponderance among the admitted cases was reported in several studies in contrast to our study finding. Exact reason for this finding is not known.…”
Section: Discussioncontrasting
confidence: 95%
See 3 more Smart Citations
“…Studies from other parts of India and other countries have reported a similar age distribution. 9,10,[18][19][20] Male preponderance among the admitted cases was reported in several studies in contrast to our study finding. Exact reason for this finding is not known.…”
Section: Discussioncontrasting
confidence: 95%
“…6,[18][19][20] Similar to other studies, fever was the predominant symptom in our study. [1][2][3][4][5][6][7][8][9][10][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] In the present study facial puffiness was noted in 45.2% of the cases, however higher proportion up to 74.62% have been reported in literature. 9,10.18,19,20 Hepatomegaly (88.6%), splenomegaly (64.5%) followed by lymphadenopathy (48.7%) and edema (43.4%) were the common signs found in this study.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…[3,4] It is a clinically important disease because it is associated with many serious complications and has a mortality rate of 14-20%. [5][6][7] Its incidence in certain parts of India reaches endemic proportions and accounts for up to 50% of undifferentiated febrile illness in those areas during cooler months of the year. [3,7] The clinical finding of a pathognomonic eschar in a patient with febrile illness is the most important clue to the diagnosis of ST.…”
Section: Discussionmentioning
confidence: 99%